2020
DOI: 10.1371/journal.pone.0236639
|View full text |Cite
|
Sign up to set email alerts
|

Maternal diabetes mellitus as an independent risk factor for clinically significant retinopathy of prematurity severity in neonates less than 1500g

Abstract: Background Retinopathy of prematurity (ROP) is a significant morbidity in preterm babies. Multiple risk factors for severe ROP have been extensively studied, however, only a few studies have included maternal diabetes mellitus (MDM) in their assessment. ROP and diabetic retinopathy are both retinal vascular diseases in which there is leakage and/or neovascularization from damaged retinal vessels. Diabetes may affect ROP development; however, there are conflicting results on the association between MDM and ROP.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 32 publications
(49 reference statements)
0
11
0
1
Order By: Relevance
“…Despite the above data, maternal diabetes was associated with an increased rate of ROP in some studies. Opara et al showed among neonates weighing < 1500 g that the risk of ROP associated with maternal diabetes was 2.64 ( p < 0.01) [ 191 ]. They assumed that there are common pathogenic mechanisms in ROP and diabetic retinopathy as both are retinal vascular diseases in which there is leakage and/or neovascularization from damaged retinal vessels [ 191 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the above data, maternal diabetes was associated with an increased rate of ROP in some studies. Opara et al showed among neonates weighing < 1500 g that the risk of ROP associated with maternal diabetes was 2.64 ( p < 0.01) [ 191 ]. They assumed that there are common pathogenic mechanisms in ROP and diabetic retinopathy as both are retinal vascular diseases in which there is leakage and/or neovascularization from damaged retinal vessels [ 191 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…Opara et al showed among neonates weighing < 1500 g that the risk of ROP associated with maternal diabetes was 2.64 ( p < 0.01) [ 191 ]. They assumed that there are common pathogenic mechanisms in ROP and diabetic retinopathy as both are retinal vascular diseases in which there is leakage and/or neovascularization from damaged retinal vessels [ 191 ]. Tunay et al also showed that maternal diabetes increased the incidence of ROP among premature infants > 1500 g and found a 25-fold and 6-fold increase in the risk of ROP and Type 1 ROP regardless of maternal diabetes type [ 192 ].…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, many centres use digital retinal photography as part of this screening process[ 65 ]. Opara et al [ 67 ] found that maternal diabetes was associated with a higher incidence of ROP. The strength of association increased with the increasing severity of ROP in preterm neonates less than 1500 mg.…”
Section: Postnatal Evaluationmentioning
confidence: 99%
“…Based on the pathogenesis, ROP and diabetic retinopathy are both retinal vascular diseases, in which there is leakage and/or neovascularization from damaged retinal vessels, based on retinal ischemia. Moreover, Opara et al [40] have suggested that maternal diabetes is associated with ROP, with the strength of association increasing with increasing severity of ROP. Ling et al [16] , however, reported that gestational diabetes did not correlate with ROP recurrences after IVR treatments.…”
Section: Discussionmentioning
confidence: 99%